Criteria of immobilization duration of the affected foot in diabetic Charcot neuro-osteoarthropathy - Anastasia Gennad'evna Demina; Vadim Borisovich Bregovskiy; Irina Al'bertovna Karpova (Сахарный диабет)
Long-term offloading is the key factor in the treatment of the acute stage of Charcot foot. The indication for remobilization and transition of the affected foot to weight-bearing activities is believed to be based on two factors: the absence of the clinical signs of inflammation and results of the objective diagnostic tests. At the present time, consensus about appropriate methods sufficient for initiating weight-bearing activities after immobilization is absent. This paper discusses current data on clinical and laboratory tests and methods and describes their advantages and disadvantages.